2012
DOI: 10.1039/c2cc35977d
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a micropatterned titania photocatalyst by microcontact printed silicatein on gold surfaces

Abstract: The enzyme silicatein has been bioengineered to carry a thiol-bearing Au-affinity tag (Cys-tag) for direct immobilization on gold carriers in shortest time without the need for prior surface functionalization. Through microcontact printing, defined silicatein micropatterns were created on gold surfaces, facilitating the subsequent enzymatically controlled synthesis of photocatalytically active TiO(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Obvious future products which should be realized include silica bers doped with titanium. Silicateins can use not only ortho-silicate and hydrolyzed TEOS but also titanium 42,31 and organotriethoxysilanes 43 as substrates. It has been demonstrated that the enzyme, under consumption of Ti[BALDH], forms an alkoxide-like conjugate of titanium and nally titanium dioxide that anneals to amorphous/partially nanocrystalline TiO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obvious future products which should be realized include silica bers doped with titanium. Silicateins can use not only ortho-silicate and hydrolyzed TEOS but also titanium 42,31 and organotriethoxysilanes 43 as substrates. It has been demonstrated that the enzyme, under consumption of Ti[BALDH], forms an alkoxide-like conjugate of titanium and nally titanium dioxide that anneals to amorphous/partially nanocrystalline TiO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…This diversity is due to the fact that in addition to functionalization of the surfaces by chemical or physical/gaseous processes, the printed material, here silicatein, can be modied to meet the given conditions. Applying again molecular biological approaches, specic tags can be applied to increase the affinity of silicatein, e.g., to gold by adding a Cys-tag to the molecule, 31 or by using a Glu-tagged silicatein which displays high affinity to hydroxyapatite. 48 The long-term goal of our studies in this eld will be the construction of a silica-based optical computer composed of optical bers with the characteristics of non-linear refractive indices and of having a small bandgap energy and, by that, allowing two-photon absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we report on the spatiotemporal control of nanoparticle growth via generation of concentration gradients using nanopatterned enzymes. Enzymes are involved in biomineralization and have been extensively used in bio‐inspired approaches because they can generate crystal growth precursors in situ and act as seeding points for nucleating new crystals . Here, we utilize the enzyme glucose oxidase (GOx) for growing gold nanoparticles as a model of crystallization of a functional material .…”
Section: Introductionmentioning
confidence: 99%
“…Silicateins are a group of hydrolytic proteins from marine sponges that can be immobilized on surfaces with the aid of various tags. [17][18][19] Silicateins catalyse the polymerization of silica, leading to the formation of biosilica in marine sponges. 20,21 Whereas the technical synthesis of siliceous materials requires high temperatures, high pressures and the use of caustic chemicals, biological systems can synthesise silica-based materials at ambient temperatures and pressures and produce an amazing diversity of precisely nanostructured morphologies.…”
mentioning
confidence: 99%